The Impact of Ownership Structure, Business Diversification and Company Size on Performance of Listed Companies in Indonesia Stock Exchange (IDX) - Masdupi, Erni (2010)
This thesis examines the impact of ownership structure, diversification of business, and company size on performance of listed companies in Indonesia Stock Exchange (IDX) between 1996 and 2005. Structural equation modeling (SEM) is utilized to answer the research questions. To verify the construct validity of the measurement model, confirmatory factor analysis (CFA) is used, i.e., to examine the fitness of the hypothesized measurement model on the data collected. The structural model then investigates the influence of ownership structure, diversification of business and company size on company performance. Based on 210 company-year observations, it is found that the hypothesized measurement model fits the data as shown by the goodness of fit indices and the significant factor loadings. The structural model showed that ownership structure, which includes insider ownership, institutional ownership, foreign ownership, and shareholder dispersion, did not affect company performance, which is represented by a latent variable which was manifested through return on equity (ROE), return on total assets (ROA) and market to book value ratio (MBVR). Similarly, diversification of business was also found to be insignificant in influencing company performance. Diversification of business could increase company performance through internal capital market, but this could not be proven in the listed companies on IDX. The only variable that had a significant and positive effect on performance of listed companies on IDX was company size. Perhaps, in an emerging market such as Indonesia, size plays a significant role in influencing company performance due to the presence of greater economies of scales, better competitive position, having more skilled managers, and having greater access to cheaper sources of funds. It means that listed companies on the IDX could increase performance by increasing their size. This implies that the regulators should adopt policies that encourage or at least do not impede companies to grow in size. Ownership structure as a mechanism to mitigate agency conflict as suggested by the agency theory could not be supported in the context of the IDX. Excessive stock ownership was not modelled for specifically in the IDX. This result was also inconsistent with the efficient monitoring hypothesis, conflict of interest and strategic alignment hypothesis, and rescue acquisition hypothesis. This might be due to differences in the rules, regulations and law enforcement in Indonesia, which might not be as stringent as those in developed markets. Investor’s protection is rather low in IDX which should reflect the reduced ability of investors to influence management decision, and thus reduce the influence of ownership structure on company performance. To reinforce the findings of SEM, regression was executed, and the analysis produced an almost similar finding. Size significantly contributed to company performance for all models while two proxies of business diversification were found to be significant in influencing two (accounting/or book value) proxies of company performance. Ownership structure did not seem to influence company performance.